DEVELOPMENT AND VALIDATION OF UV SPECTROSCOPIC METHOD FOR ESTIMATION OF ABACAVIR IN TABLET DOSAGE FORM - TOKEY, AKHILESH S.; SURYAWANSHI, MUGDHA R.; TAMBE, PRANAV P. (International Journal of Current Pharmaceutical Research, 2022)
Objective: To develop and validate simple, rapid, linear, accurate, precise and economical UV Spectroscopic method for estimation of Abacavir in tablet dosage form. Methods: The drug is freely soluble in analytical grade methanol. The drug was identified in terms of solubility studies and on the basis of melting point done on the melting point apparatus of Equiptronics. It showed absorption maxima were determined in analytical grade methanol. The drug obeyed the Beer’s law and showed good correlation of concentration with absorption, which reflect in linearity. The UV spectroscopic method was developed for estimation of Abacavir in tablet dosage form and also validated as per ICH guidelines. Results: The drug is freely soluble in analytical grade methanol, slightly soluble in water and practically insoluble in ethanol. So, the analytical grade methanol is used as a diluent in method. The melting point of Abacavir was found to be 164-165 ˚C (uncorrected). It showed absorption maxima 256 nm in analytical grade methanol. On the basis of absorption spectrum the working concentration was set on 15µg/ml (PPM). The linearity was observed between 5-25 μg/ml (PPM). The results of analysis were validated by recovery studies. The recovery was found to be 98.75, 101 and 99.17% for three levels respectively. The % RSD for precision was found to be 0.32% and for Ruggedness is 0.46% Conclusion: A simple, rapid, linear, accurate, precise and economical UV Spectroscopic method has been developed for estimation of Abacavir in tablet dosage form. The method could be considered for the determination of Abacavir in quality control laboratories.